The Association Between Facial Width-to-Height Ratio (fWHR) and Sporting Performances: Evidence From Professional Basketball Players in Japan - Sato, Shintaro; Kinoshita, Keita; Sekino, Koichi; Amano, Haruka; Bizen, Yoshifumi; Matsuoka, Hirotaka (Frontiers in Psychology, 2021)
Previous research has highlighted the potential role of facial structures in explaining human behavior. The facial width-to-height ratio (fWHR) was found to be associated with testosterone-driven behavioral tendencies like achievement drive, aggression, and sporting success. The authors in the current study aimed to replicate such relationships using real-world data (i.e., professional basketball players; N = 482). Achievement drive, aggression, and sporting success were operationalized as field-goal attempts (FGA), the number of fouls committed (Foul), and player performance rating (EFF), respectively. The results indicated that fWHR was significantly associated with FGA and EFF, controlling for minutes of play and body-mass-index (BMI). The same results were obtained for separate analyses focusing on outsider players. However, analyses of inside players demonstrated that fWHR was associated only with EFF. The current research further provides empirical evidence supporting the effects of fWHR on achievement drive and sporting successes, although the effect sizes are notably small.